Accommodations, modifications, and special education interventions: influence on teacher expectations. Issue 5 (17th November 2022) - Sahli Lozano, Caroline; Brandenberg, Kathrin; Ganz, Anne Sophie; Wüthrich, Sergej
ABSTRACT: Students with special educational needs (SEN) are at risk of lower teacher expectations due to disability-related negative labelling effects. In most educational systems, students with SEN receive measures such as accommodations (adjustments of the learning/assessment conditions), curriculum modifications (adjustments of the learning objectives), or additional support from special education teachers to support inclusion in regular school. Here, we examine whether the receipt of such measures, even in the absence of a formally assessed SEN or disability diagnosis, is sufficient to evoke negative labelling effects. Using data from 110 lower secondary school classes in Switzerland, we show that students with reduced learning objectives or individual support by a special education teacher get systematically underestimated by their teachers regarding their cognitive abilities, although this is not the case for students receiving accommodations. These findings provide important implications for the application of such measures and the prevention of educational inequalities.